Identification of most suitable temperature humidity index model for daily milk yield of Murrah buffaloes in subtropical climatic condition of India - BEHERA, RAJALAXMI; CHAKRAVARTY, A K; KASHYAP, N; BHARTI, BHARTI; RAI, S; MANDAL, A; SINGH, AVTAR; GUPTA, A K (The Indian Journal of Animal Sciences, 2018)
The present study was carried out to identify the most suitable temperature humidity index (THI model) among seven reported THI models as heat stress indicator on daily milk yield (DMY) of Murrah buffaloes at subtropical climatic conditions of Karnal, India. A total of 302,101 daily milk yield records from 1,434 lactational milk yield records and pedigree records of 748 buffaloes belonging to five parities spanned over a period of about 20 years (March 1994-December 2013) were obtained from ICAR-NDRI, Karnal and weather information on dry bulb temperature (Tdb), wet bulb temperature (Twb) and relative humidity (RH in %) for the corresponding period were collected from ICAR-CSSRI, Karnal. The overall least-squares mean for daily milk yield was 7.55±0.002 kg. Average daily THI was computed using each of the seven models under study. Regression analysis was performed to determine the most suitable THI model for assessing the effect of heat stress on DMY and a negative association was found between DMY (kg) and THI. THI model 5 developed by NRC (1971) was identified as the most suitable THI model to study the impact of thermal stress on DMY of Murrah expressing maximum decrease in DMY (-0.029 kg) per unit rise in THI.